2010
DOI: 10.1111/j.1365-2591.2010.01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term sealing ability of resin‐based root canal fillings

Abstract: AH Plus/gutta-percha provided superior root canal sealing at both immediate and 180-day time periods. The presence of a coronal seal reduced leakage significantly. Storage of root filled specimens did not disturb the sealing ability of the tested materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
(73 reference statements)
1
38
0
2
Order By: Relevance
“…Restorative dentistry concepts using adhesive materials have increasingly been applied to endodontics to prevent coronal leakage (2,11), such as use of fibre posts in the restoration of endodontically treated teeth (14), and even for the filling of the root canal (15). The use of these materials is based on the premise that because of the intimate contact with dentine, these materials could remain micromechanically retained, reinforcing tooth structure and preventing root contamination (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Restorative dentistry concepts using adhesive materials have increasingly been applied to endodontics to prevent coronal leakage (2,11), such as use of fibre posts in the restoration of endodontically treated teeth (14), and even for the filling of the root canal (15). The use of these materials is based on the premise that because of the intimate contact with dentine, these materials could remain micromechanically retained, reinforcing tooth structure and preventing root contamination (16).…”
Section: Discussionmentioning
confidence: 99%
“…Some characteristics as ease and speed of placement, sealing efficacy, and high bond strength qualify the ideal restorative material to barrier (11), and the use of dentin bonding agents has been advocated to help provide a better intracoronal seal (12). Therefore the aim of this in vitro study was to evaluate the ability sealing of glass ionomer and composite resin with or without 1-mm thickness of Coltosol on the root-canal filling material.…”
Section: Introductionmentioning
confidence: 99%
“…No difference was detected between coronal restorative materials: Coltosol or Clearfil SE Bond. 97 Another study has shown the same results by using glass-ionomer. 98 …”
Section: Introductionmentioning
confidence: 63%
“…[80][81][82][83][84][85][86][87][88][89][90] However, analysis of leakage studies must be carried out with caution as a 'superior' result has a different meaning depending on the technique employed. For example, in a dye penetration test a published; these studies form the bulk of the scientific research on Resilon.…”
Section: Sealing Ability/leakagementioning
confidence: 99%